1974
DOI: 10.1037/h0037256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social class, moral orientation, and severity of punishment on boys' moral responses to transgression and generosity.

Abstract: In two experiments, the effects of social class, moral orientation, and severity of punishment on boys' moral responses to transgression and generosity were investigated in second-and third-grade boys. In Experiment 1, a modified version of Aronfreed's task, the response measures were the self-critical and reparative responses on the transgression trial, the self-critical responses prior to this trial, and the number of candies removed by the subject during the task. In Experiment 2, the subject was asked if h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…However, the effects of punishment intensity on self-judgments differ depending upon whether the behavior judged is related (cf. DePalma, 1974) or unrelated to the behavior previously punished by the experimenter. Instead of a possible modeling effect in which highly punished subjects punished themselves greatly (e.g., DePalma, 1974), self-judgments were significantly more favorable after high punishment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effects of punishment intensity on self-judgments differ depending upon whether the behavior judged is related (cf. DePalma, 1974) or unrelated to the behavior previously punished by the experimenter. Instead of a possible modeling effect in which highly punished subjects punished themselves greatly (e.g., DePalma, 1974), self-judgments were significantly more favorable after high punishment.…”
Section: Discussionmentioning
confidence: 99%
“…DePalma, 1974) or unrelated to the behavior previously punished by the experimenter. Instead of a possible modeling effect in which highly punished subjects punished themselves greatly (e.g., DePalma, 1974), self-judgments were significantly more favorable after high punishment. These results indicate that the influence of modeling effects must be considered in any future studies involving self-judgments following punishment if the behavior punished experimentally is similar to that to be judged by the subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While positive relationship~ between reasoning and verbalizations and altruism have been reported (Rice and Grusec 1975;Hoffman 1963;Depalma 1974;Hoffman and Saltzstein 1967), not all studies support this conclusion (Grusec and Skubiski 1970;Staub 1971;Olejnik and McKinney 1973). With regard to the analogue studies, the lack of broad measures of altruism and the reliance on the paradigms of sharing improbable objects with absent needy children further weaken the conclusions which can be made.…”
mentioning
confidence: 97%
“…More recently, Depalma (1974), in a study of donating behavior in the laboratory, found that higher intensity punishment (e.g., a larger number of candies taken away for a tra~sgression) elicited greater donating behavior than low intensity punishment. However, children whose moral orientation reflected parents who emphasized induction donated more than those children whose moral orientation reflected parents who emphasized power assertion, regard- When all indices of moral development were combined .…”
mentioning
confidence: 99%